Association between Obesity and Markers of Inflammation, Oxidative Stress and Neuronal Injury in Women with Non-alcoholic Fatty Liver - Moushira Zaki (Journal of Global Pharma Technology, 2019)
The present study aimed to investigate the association of Nuclear Factor (NF)-κB, oxidized –low density lipoprotein (o-LDL), total antioxidant capacity (TAC), neuron-specific enolase (NSE) and CD4 in obese women with non-alcoholic fatty liver (NAFLD). A total of 36 NAFLD obese women were enrolled in this study and 36 female control healthy women (aged 30-39) without cognitive impairment were examined. NAFLD patients were diagnosed by magnetic resonance elastography. Anthropometric parameters including body height, weight, waist circumference (WC) and body fat % were measured. Serum NF-Κb, TAC, CD4, o- LDL and NSE were measured by ELISA. Also, liver function tests, lipid profile were done. The present results showed marked elevation in serum NF-κB and o-LDL, while significant reduction in TAC and CD4 in obese NFALD than normal control subjects. In conclusion results provide evidence of association between obesity, high levels of oxidative stress, inflammatory markers and brain biomarker in women with NAFLD.